Pengaruh Emotional Intelligence, Pola Komunikasi, Dan Kepemimpinan Transformasional Terhadap Kinerja Pegawai - Sugeng Widakdo; Mawar Hidayanti (Universitas Sains dan Teknologi Komputer, 2024)
Performance is the employee's ability to complete work during the activity period according to the standards determined by the organization. Employee performance will be effective and efficient if interactions with co-workers and superiors are open, that is, giving freedom to express thoughts and ideas as a form of feeling supported by superiors who are always able to encourage and pay attention to seeing work challenges into opportunities. This research aims to determine the influence of emotional intelligence, communication patterns and transformational leadership on the performance of Bima Housing and Settlement service employees. The population in this study were 63 employees at the Bima Housing and Settlement Department, especially the Bima City Housing, Settlement and Land Department, with a sampling technique using purposive sampling, namely 38 civil servant employees as respondents.Data collection techniques using questionnaires. The data analysis technique uses multiple linear regression analysis with the help of SPSS version 27. The results of this study partially show that the emotional intelligence variable has a negative and insignificant effect on employee performance, the communication pattern variable has an insignificant effect on employee performance, and the transformational leadership variable has a positive and significant effect on performance. employee. Simultaneously, the variables emotional intelligence, communication patterns and transformational leadership have a positive and significant effect on employee performance Emotional Inteligence, Communication Patterns, Transformasi Leadership, Performance